Harmonising equity and efficiency in allocating global post-Kyoto GHG emissions. (8th February 2010) - Lozano, Sebastian; Gutierrez, Ester
In this paper, a non-parametric efficiency analysis approach is presented for determining Greenhouse Gases (GHG) tradable emissions allowances for all countries. The approach has two steps: expansion and contraction. In the expansion step and given its population, each country is projected on the efficient frontier and a maximum GDP and associated energy and GHG emissions levels are computed. Since the sum of these expanded GHG emission levels exceeds the available global emissions budget, a uniform reduction is hence applied to all countries to determine their emissions quota. This contraction step determines for each country the maximum GDP (and associated energy consumption) that can be achieved given its population and its GHG emissions allowance. Results for 183 countries and using 2025 as reference year are presented and discussed.